The COVID-19 pandemic from an acute psychiatric perspective: a London psychiatric intensive care unit experience. (April 2021) - Skelton, Luke; Pugh, Ria; Harries, Bethan; Blake, Lucy; Butler, Margaret; Sethi, Faisil
Summary: The COVID-19 pandemic has put the UK's National Health Service under extreme pressure, and acute psychiatric services have had to rapidly adapt to a new way of working. This editorial describes the experience of a London psychiatric intensive care unit (PICU) where all nine in-patients ultimately tested COVID-19 positive.